Nature and outcome of Nigeria's #notosocialmediabill twitter protest against the frivolous petitions bill 2015 (2017)
Focusing on the #NoToSocialMediaBill Twitter protest against the introduction of The Frivolous Petitions (Prohibition, etc.) Bill 2015, in Nigeria, this chapter examined the composition of the loudest voices that framed the protest, explored the level of engagement of those voices with the content of the bill, and analysed the nature and outcome of the protesters' reactions to the bill. To achieve these objectives, the study adopted a mixed method sequential design consisting of quantitative and qualitative content analyses with framing as the theoretical framework. Findings show that hashtag and retweet features of Twitter together functioned effectively as collective framing tools in the #NoToSocialMediaBill Protest. However, the protesters adopted fear-induced collective frames that ignored the contents of the bill. Though the frames drew global media and human rights activists' attention in support of the protesters' goal of resisting an attempt to restrict freedom of speech, they did not achieve the same with the recall of the initiator of the bill.